Pharmacodynamic and pharmacokinetic effects of flumazenil and theophylline application in rats acutely intoxicated by diazepam - Šegrt Zoran; Đorđević Snežana; Jaćević Vesna; Kilibarda Vesna; Vučinić Slavica; Jović-Stošić Jasmina; Potrebić Olivera; Vukčević-Perković Nataša (Vojnosanitetski Pregled, 2009)
Background/Aim. The majority of symptoms and signs of acute diazepam poisoning are the consequence of its sedative effect on the CNS affecting selectively polisynaptic routes by stimulating inhibitory action of GABA. The aim of the present study was to examine the effects of combined application of theophylline and flumazenil on sedation and impaired motor function activity in acute diazepam poisoning in rats. Methods. Male Wistar rats were divided in four main groups and treated as follows: group I - with increasing doses of diazepam in order to produce the highest level of sedation and motor activity impairment; group II - diazepam + different doses of flumazenil; group III - diazepam + different doses of theophylline; group IV - diazepam + combined application of theophylline and flumazenil. Concentrations of diazepam and its metabolites were measured with LC-MS. The experiment was performed on a commercial apparatus for spontaneous motor-activity registration (LKBFarad, Sweden). Assessment of diazepam- induced neurotoxic effects and effects after theophylline and flumazenil application was performed with rotarod test on a commercial apparatus (Automatic treadmill for rats, Ugo Basile, Italy). Results. Diazepam in doses of 10 mg/kg and 15 mg/kg produced long-time and reproducible pharmacodynamic effects. Single application of flumazenil or theophylline antagonized effects of diazepam, but not completely. Combined application of flumazenile and theophylline resulted in best effects on diazepaminduced impairment of motoric activity and sedation. As a result of theopylline application there was better elimination of diazepam and its metabolites. Conclusion. Combined application of flumazenil and theophylline resulted in the best antidotal effects in the treatment of diazepam poisoned rats. These effects are a result of different mechanisms of their action, longer half-life of theophylline in relation to that of flumezenil and presumably the diuretic effect of theophylline.